Judicial Discretion and Statutory Sentencing Limits in Juvenile Premeditated Murder Cases - Yemima Kesia Kerenhapuk Tandipayuk (The Indonesian Journal of International Clinical Legal Education, 2025)
Legal protection for children in conflict with the law is normatively regulated within the Indonesian legal system, particularly through Law Number 11 of 2012 on the Juvenile Criminal Justice System. Nevertheless, existing scholarship largely addresses juvenile protection in general terms and has not sufficiently examined the doctrinal tension between judicial discretion and statutory sentencing limits in cases involving serious crimes committed by juveniles. This study analyzes the scope of legal protection afforded to juvenile offenders involved in premeditated murder and critically examines judicial reasoning in imposing prison sentences that exceed the maximum limits prescribed by law. Employing a normative juridical research method with statute, case, and conceptual approaches, this study finds that although formal and material safeguards for juvenile offenders are clearly established in legislation, their application in judicial practice remains inconsistent. Courts frequently invoke substantive justice considerations and the combined theory of sentencing objectives to justify sentences exceeding statutory limits, primarily on grounds of social protection and deterrence. This article argues that such practices reflect a doctrinal inconsistency within Indonesia’s juvenile justice system, as they contravene the principle of legality and undermine the child-protection orientation mandated by Article 81 paragraph (6) of Law Number 11 of 2012. This study contributes to juvenile justice discourse by proposing the necessity of clearer sentencing guidelines and strengthened judicial oversight to prevent excessive judicial discretion and to ensure the consistent implementation of child protection principles.